(untitled) (Journal of Oriental Studies, 2016)
The article discusses the main force of imperialism in Turkey and Arab countries, and political aspects of the relationship between the countries of the Middle East. Based on the latest research based framework of political portraiture of these countries, as well as the comparative analysis.